Case Report: Pathologic Complete Response to Induction Therapy in a Patient With Potentially Resectable Pancreatic Cancer - Lu, Changchang; Zhu, Yahui; Cheng, Hao; Kong, Weiwei; Zhu, Linxi; Wang, Lei; Tang, Min; Chen, Jun; Li, Qi; He, Jian; Li, Aimei; Qiu, Xin; et al. (Frontiers in Oncology, 2022)
Immune-monotherapy does not appear to work in patients with pancreatic cancer so far. We are conducting a clinical trial that combines PD-1 inhibitor with chemotherapy and concurrent radiotherapy as induction therapy for patients with locally advanced (LAPC) and borderline resectable pancreatic cancer (BRPC). Here, we performed a case with pathologic complete response(pCR) and no postoperative complications after the induction therapy. The patient received four cycles of induction therapy and achieved partial response (PR) with significant decline of tumor markers CA19-9. Also, peripheral blood samples were collected during the treatment to investigate serial circulating tumor DNA (ctDNA) dynamic changes in predicting tumor response and outcomes in patients. Our result suggested that PD-1 blockade plus chemotherapy and concurrent radiotherapy is a promising mode as induction therapy for patients with potentially resectable pancreatic cancer. In this case, serial ctDNA alterations accurately provide a comprehensive outlook of the tumor status and monitor response to the therapy, as validated by standard imaging.